Insights from the New Zealand Experience of Farmer First Research. (September 2014) - Reid, Janet; Brazendale, Rob
The Farmer First Research (FFR) programme was established at Massey University in 1991 and ended in 1996. It represented a fundamental shift in how agricultural research priorities were set and implemented. Farmers' needs and circumstances were central to defining research priorities, and the active involvement of farmers was pivotal. In 2012, the New Zealand government invested significantly in the Primary Innovation (PI) project, the aims of which were similar to those of the FFR programme. This paper critically reflects on the FFR programme and highlights lessons to inform the PI project. The authors argue that poor actor engagement and limited broader legitimacy and support have constrained the programme's influence on sustained change in the innovation system that prevailed at the time. Also highlighted is the critical importance of actors and interactions when a programme that seeks institutional and infrastructural change is being established and developed.